Hazard analysis on chemical usage toward the workers productivity in oil palm plantation / Mohd Afzan Maliki - Maliki, Mohd Afzan (Faculty of Plantation and Agrotechnology, 2017)
Hazard analysis on chemical usage toward the workers is a systematic approach in identification, assessment and control of hazard in the plantation sector. The high usage of chemical were effect on the workers daily life, and dangerous for a long term which will lead to the reduce of productivity. Regarding the matter, the aims of the study is to carried out the impacts of chemical usage to the workers’ health, cost, technique and environment. The method was conduct by using structural questionnaire to the 48 sample out of 50 workers. Form this study it found that there are not significant different between chemical usage towards workers productivity because the significant value was 0.790. The most impact of chemical usage was health of workers and there were no relationship between all impacts with workers productivity since p-value more than 0.05.